PASSING OVER TEOLOGI BERAGAMA (Studi Esoterisme Agama-agama) - ., A k h i y a t (Inovasi: Jurnal Diklat Keagamaan, 2017)
A person’s knowledge of religion has different understanding levels of.The differences can be caused by various dimensions. Startingfrom personal experience, normative religious knowledge, as wellas religious knowledge historically. When one’s understandingcan only rely on one-dimensional understanding, when he/shejudges others always assumes those who disagree with him are accusedas heresy, and out of the religious rail corridor. To explore the vastocean of knowledge in religion requires the freedom of the soul, thisattitude will lead people beyond the boundaries of the religions. Notonly explore the understanding of a religious course, but also be able toexplore various cultures and understanding of other religions. Someof them, have dared to explore the limits of inter-religions, where whathe got was a ”universal” understanding. Understanding and personalexperience that can not be expressed in words. Through the study ofreligions, we can be find similarities among others. Those are maturityattitude and be able to understand of other religions. In a contras, thosewhose faith is only based on exoteric understanding only, it meanshis religion’s understanding or merely on textual religion understanding.